Intermediary role performance analysis of Malaysian Islamic and conventional banks - Fauzias Mat Nor; Amir Shaharuddin; Norhaziah Nawai; Ainulashikin Marzuki; W Zainuddin Wan Abdullah (Penerbit Universiti Kebangsaan Malaysia, 2018)
The objective of this paper is to investigate the effect of bank specific characteristics and macroeconomics variables on bank margin (NIM) which reflects the intermediary role of Islamic and conventional banks in Malaysia for the period of 2006 to 2014. By using static panel analysis, the results show that management efficiency is positively related to the bank margin for both Islamic and conventional banks. For Islamic banks, bank size and liquidity ratio have significant negative relationship on bank margin. The default risk is positively related to bank margin for Islamic banks. As for conventional bank, the non interest to total asset ratio has significant positive relationship on bank margin. Therefore, the results show that there are similarities and differences in terms of determinant factors that affect the bank margin between Islamic banks and conventional banks. These empirical results suggest an important policy on issues pertaining to how Islamic and conventional banks have to adjust the changes in the banking environment. The conventional banks have more comparative advantages specifically on management efficiency as its intermediary role performance is also not affected by size.